“Capital investment anomaly” and “Accruals anomaly” : independent or inter-dependent? – evidence from South Asia - Abdul Rafay; Ramla Sadiq; Shahzeb Ahmed (Penerbit Universiti Kebangsaan Malaysia, 2017)
The purpose of this research is to determine the impact of “Capital investment anomaly” and “Accrual anomaly” on stock returns after controlling the size and book-to-market effects. This study aims to fill a gap regarding the implications of capital investment anomaly and accrual anomaly in South Asian economies, and primarily focused on two developing economies from SAARC region; India and Pakistan. This study uses 320 company-year observations using a sample period of 2009-2014. The sample is representative of 50% of non-financial companies selected systematically from nine different sectors included in Pakistan Stock Exchange (KSE-100 index) and Bombay Stock Exchange (BSE-100 index) each. Selection is based on market capitalization to mitigate any bias in results. Preliminary analysis includes understanding stock performance of capital investment-based, and accrual-based portfolios, followed by stock performance of combined effect portfolios, and sector analysis. Lastly, regression analysis allows determining impact of both anomalies on returns as well as their independence or interdependence. The results of this study show that there exists a negative relationship between Stock Returns and Capital Investment/Accruals. In addition to this, we found that both anomalies are not distinct and work together and are attributed to country characteristics specific to the SAARC/South Asia region. All of the coefficients are statistically significant. The separate results for India and Pakistan are helpful for practitioners to know what strategy to adopt in order to maximize the returns. Combined results are beneficial for prospective investors. The mixed trend of returns for different sectors is useful for both managers and investors in the sense that both anomalies are independent of each other. From a theory development perspective, it reveals the differences in existing literature due to change in geographical context